2019
DOI: 10.1099/mgen.0.000306
|View full text |Cite
|
Sign up to set email alerts
|

Emergence, molecular mechanisms and global spread of carbapenem-resistant Acinetobacter baumannii

Abstract: Acinetobacter baumannii is a nosocomial pathogen that has emerged as a global threat because of high levels of resistance to many antibiotics, particularly those considered to be last-resort antibiotics, such as carbapenems. Although alterations in the efflux pump and outer membrane proteins can cause carbapenem resistance, the main mechanism is the acquisition of carbapenem-hydrolyzing oxacillinase-encoding genes. Of these, oxa23 is by far the most widespread in most countries, while oxa24 and oxa58 appear t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
330
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(374 citation statements)
references
References 161 publications
16
330
0
Order By: Relevance
“…This study showed that all Iranian outbreak strains belong to the same sequence type, ST328 in the Institut Pasteur scheme, and share many properties, such as resistance to the frontline carbapenem antibiotics, conferred by the carbapenem resistance oxa23 gene in Tn2006 within AbaR4, which is located in the chromosomal comM gene, and a plasmid that carries oxa24. This study further represents the first analysis of the genetic context of the most widespread carbapenem resistance gene, oxa23 (19), in A. baumannii isolates recovered from Iran. In A. baumannii strains that belong to the two major global clones, resistance genes often reside in the chromosome within large genomic islands (6, 23, 24).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This study showed that all Iranian outbreak strains belong to the same sequence type, ST328 in the Institut Pasteur scheme, and share many properties, such as resistance to the frontline carbapenem antibiotics, conferred by the carbapenem resistance oxa23 gene in Tn2006 within AbaR4, which is located in the chromosomal comM gene, and a plasmid that carries oxa24. This study further represents the first analysis of the genetic context of the most widespread carbapenem resistance gene, oxa23 (19), in A. baumannii isolates recovered from Iran. In A. baumannii strains that belong to the two major global clones, resistance genes often reside in the chromosome within large genomic islands (6, 23, 24).…”
Section: Discussionmentioning
confidence: 84%
“…CRAB was placed as the number 1 critical priority pathogen on the World Health Organization's list of 12 multiresistant bacteria for which immediate research on new therapeutics and antibiotic development is required (44). However, despite the global distribution of CRAB and the need to have data from all countries, there is a substantial gap in WGS data from most geographical regions across the globe, as the bulk of the current publicly available genome sequence data is from only 4 countries, namely, the United States, China, Thailand, and Australia (19). The lack of sequence data has made it difficult to track the spread of resistance at the global level and determine the population structure of this microorganism (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an important limitation of our study. We evaluated A. baumannii belonging to international STs such as ST15 and ST297 [28,29] as well as S. marcescens carrying KPC-the most frequent carbapenemase described for this organism [1,2]. Thus, our findings can be useful internationally.…”
Section: Discussionmentioning
confidence: 99%
“…The population of MDR-AB is characteristic of clonal dissemination, as revealed by multi-locus sequence typing (MLST). Clonal complex (CC) 2 is by far the most widely disseminated A. baumannii population in more than 30 countries, including China [8], and ST2 is dominant in CC2 [9]. ST2 has been reported to be associated with antimicrobial resistance [10][11].…”
Section: Introductionmentioning
confidence: 99%